2021
DOI: 10.1097/md.0000000000028396
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of postoperative stricture after endoscopic submucosal dissection for superficial esophageal neoplasms

Abstract: Background: As larger-sized superficial esophageal neoplasms became candidates for endoscopic submucosal dissection (ESD), post-ESD esophageal stricture has inevitably developed into a significant complication during long-term follow-up. Method: The PubMed, Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, Web of Science, as well as China National Knowledge Infrastructure, the Wanfang Database, and the Chinese Biomedical Literature Database, were searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Endoscopic resections comprising > 50 % of the esophageal luminal circumference are prone to stricture formation, and after full circumferential resection strictures occur in almost all patients [138][139][140]. A meta-analysis found that upper third location (OR 1.5), IIa/IIc morphology (OR 2.8), tumor deeper than m1 (OR 7.5), tumor deeper than m2 (OR 12.7), circumferential extent > 3/4 (OR 38), and longitudinal length (mean difference 13.7 mm) are risk factors for stricture development [141].…”
Section: Esophagusmentioning
confidence: 99%
“…Endoscopic resections comprising > 50 % of the esophageal luminal circumference are prone to stricture formation, and after full circumferential resection strictures occur in almost all patients [138][139][140]. A meta-analysis found that upper third location (OR 1.5), IIa/IIc morphology (OR 2.8), tumor deeper than m1 (OR 7.5), tumor deeper than m2 (OR 12.7), circumferential extent > 3/4 (OR 38), and longitudinal length (mean difference 13.7 mm) are risk factors for stricture development [141].…”
Section: Esophagusmentioning
confidence: 99%
“…This study demonstrates the efficacy of a systematic prospective protocol to prevent post-ESD esophageal strictures in a Western tertiary center. Without preventive measures, stricture rates can reach 70% to 100% [15], especially when the degree of resection is greater than 75% of the esophageal circumference [3,4,18]. Among the currently used preventive methods, local steroid injection and oral steroids are standard treatments since they have demonstrated efficacy for prevention of strictures and the need for endoscopic balloon dilation [4,12,13,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent review, 11 existing studies focused on predicting post‐ESD esophageal stricture 10 . However, most of these studies focused on a selection of factors, and no study has developed a nomogram yet.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported other risk factors, including longitudinal length of the tumor, invasion depth deeper than lamina propria mucosa (m2), and propria muscularis injury 7–9 . A recent review including 11 existing studies reported the following six substantial risk factors: lesion characteristics involving the upper third of the esophagus, IIa/IIc macroscopic Paris type, tumor invasion depth as deep as or deeper than the m2, tumor length, circumferential diameter, and circumferential range more than 75% 10 . No studies to date that include all of these relevant factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation